Impurity concentration behaviors in a boiling tubesheet crevice - Part II. Packed crevice - Bahn, CB; Oh, SH; Park, BG; Hwang, IS; Rhee, IH; Kim, UC; Na, JW (ELSEVIER SCIENCE SA, 2003)
The impurity concentration behavior of a boiling crevice packed with magnetite particles was investigated with thermocouples and electrodes for the measurement of temperature and electrochemical corrosion potential (ECP), respectively, in order to understand chemical change in a pressurized water reactor (PWR) steam generator (SG) crevice. A secondary solution composed of 50 ppm Na and 200 ppb hydrogen was supplied at a flow rate of about 4 l/h. Sodium hydroxide (NaOH) concentration process in the crevice and the resultant boiling point elevation behavior were characterized with temperature and ECP data. The temperature in the packed crevice was about 2-3 degreesC higher than that for the open crevice. In the same conditions, the magnetite-packed crevice showed a greater amount of boiling point elevation with a longer time to reach a steady state compared with the case of an open crevice. It was found that the bottom region of the crevice was initially filled with steam, and then the concentrated liquid region initially located at the middle of crevice expanded to both the crevice bottom and the upper region. To analytically estimate the wetted length, a closed form model was introduced. The model results estimated the initial wetted length shorter as compared with the measurement results. Measured ECP results of packed crevice showed similar behaviors as compared with calculated results by using Nernst equation. ECP results reasonably coincided with the boiling point elevation estimated from the temperature data except one unusual case. (C) 2003 Elsevier B.V. All rights reserved.